2001
DOI: 10.1002/ps.354
|View full text |Cite
|
Sign up to set email alerts
|

Cytochromes P450 of insects: the tip of the iceberg

Abstract: The cytochrome P450-dependent monooxygenases are an extremely important metabolic system involved in the metabolism of endogenous compounds and xenobiotics. Collectively, P450 monooxygenases can metabolize numerous substrates and carry out multiple oxidative reactions. The large number of substrates metabolized is due to the plethora of P450 isoforms and to the broad substrate specificity of some isoforms. Monooxygenases of insects have several functional roles, including growth, development, feeding and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
182
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(192 citation statements)
references
References 110 publications
(171 reference statements)
4
182
0
6
Order By: Relevance
“…Additionally, different forms of P450s participate in the metabolism of different molecules, such as sterols, steroid hormones and several lipids that include eicosanoids, vitamin D3 and retinoid (Simpson 1997). In insects, P450s also participate in a variety of physiological roles ranging from development, feeding and growth to resistance to pesticides and tolerance to plant toxins (Scott & Wen 2001, Gilbert 2004. P450s are intimately involved in the synthesis and degradation of hormones and pheromones, such as 20-hydroxyecdysone and juvenile hormone (Scott & Wen 2001, Gilbert 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, different forms of P450s participate in the metabolism of different molecules, such as sterols, steroid hormones and several lipids that include eicosanoids, vitamin D3 and retinoid (Simpson 1997). In insects, P450s also participate in a variety of physiological roles ranging from development, feeding and growth to resistance to pesticides and tolerance to plant toxins (Scott & Wen 2001, Gilbert 2004. P450s are intimately involved in the synthesis and degradation of hormones and pheromones, such as 20-hydroxyecdysone and juvenile hormone (Scott & Wen 2001, Gilbert 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In insects, P450s also participate in a variety of physiological roles ranging from development, feeding and growth to resistance to pesticides and tolerance to plant toxins (Scott & Wen 2001, Gilbert 2004. P450s are intimately involved in the synthesis and degradation of hormones and pheromones, such as 20-hydroxyecdysone and juvenile hormone (Scott & Wen 2001, Gilbert 2004). P450s expressed in oenocytes might participate in steroid metabolism, as previous data has demonstrated that oenocytes isolated from Tenebrio molitor larvae can synthesise both α and β ecdysone from 4-14 C-cholesterol precursors in vitro (Romer et al 1974).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytochrome P450s are an ancient protein family found in all forms of life (Scott and Wen 2001;Sztal et al, 2012) and are known to be the major phase I metabolizing enzymes. In humans, CYPs metabolize approximately 65% of currently used clinical drugs (Zhou et al, 2005), emphasising the importance of this group of enzymes in xenobiotic metabolism.…”
Section: Introductionmentioning
confidence: 99%